An empirical assessment of monetary policy channels on income and wealth disparities - Alves, José (2020)
Our paper aims at analysing the relation between monetary policy and its transmission channels on both income and wealth inequality for the Euro Area. We analysed three different channels identified by the literature (Income, Portfolio and Earnings Heterogeneity) that might explain how monetary policy decisions may affect wealth and income distribution. In this empirical research we also set up a fourth regression combining all our selected explanatory variables with the goal of studying the impact of the aforementioned channels combined. For income inequality we analysed four different measures, namely Gini of disposable income (GDI), Gini of market income (GMI), share of income held by the top 1% and the share of income of the top 10% of society. In what regards to wealth inequality due to lack of data we had to create an alternative measure that can both translate the unequal savings rate of the Euro Area countries and evaluate the pace of capital accumulation in order to shed a light on the gap between high-income and low-income household’s annual savings. So that our study could be conducted we developed an unbalanced panel data analysis for the Eurozone countries between 1999 and 2017. The results we reached led us to conclude that the increase in asset prices, mainly equity, seems to be relevant to explain an increase in income inequality. However, it seems that the positive impact that MP had on unemployment by reducing it, contributed to avoid a higher increase on income inequality in the Euro Area.